2010
DOI: 10.1074/jbc.m110.144121
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of HIV-1 gp120-CD4 Receptor Complex through Targeted Interchain Disulfide Exchange

Abstract: HIV-1 enters cells via interaction between the trimeric envelope (Env) glycoprotein gp120/gp41 and the host cell surface receptor molecule CD4. The requirement of CD4 for viral entry has rationalized the development of recombinant CD4-based proteins as competitive viral attachment inhibitors and immunotherapeutic agents. In this study, we describe a novel recombinant CD4 protein designed to bind gp120 through a targeted disulfide-exchange mechanism. According to structural models of the gp120-CD4 receptor comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…In nonreducing SDS-PAGE, C35NDs60c showed mainly as monomers (60.5 kDa) (Fig. 1b, lane 3), although oligomers were detected, some of which likely formed in nonreducing conditions (8). The 214.8-kDa complex in the AUC indicated that C35NDs60c existed mainly as tetramers.…”
Section: Design and Construction Of Plasmids Expressing Recombinant Cmentioning
confidence: 99%
“…In nonreducing SDS-PAGE, C35NDs60c showed mainly as monomers (60.5 kDa) (Fig. 1b, lane 3), although oligomers were detected, some of which likely formed in nonreducing conditions (8). The 214.8-kDa complex in the AUC indicated that C35NDs60c existed mainly as tetramers.…”
Section: Design and Construction Of Plasmids Expressing Recombinant Cmentioning
confidence: 99%
“…5B). In contrast, 2dCD4-WT preparations (30 -40% of the content of which is oxidized in D1 and D2) show far more regular and ordered ␤-pleating patterns (27,(41)(42)(43). This suggests that a degree of structural flexibility in CD4, potentially conferred through CD4 disulfide reduction, may be required for the initial engagement with gp120.…”
mentioning
confidence: 60%
“…2dCD4 Redox Isomer Analysis-We previously reported the production of a recombinant protein containing the first two N-terminal domains of human CD4 (2dCD4-WT) using an E. coli-based expression system (27). Following extraction from inclusion bodies, purification by nickel-nitrilotriacetic acid affinity chromatography and refolding under conditions that promote disulfide bond formation, functional 2dCD4-WT can be prepared to apparent homogeneity, resolving as a single band of ϳ28 kDa when analyzed by denaturing, reducing SDS-PAGE (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerutti et al (53) showed that a recombinant two-domain CD4 variant containing an S60C mutation could be covalently linked to gp120, probably through the Cys 126 -Cys 196 disulfide bond at the stem of the V1/V2 variable loop, as this cystine is well positioned to react with Cys 60 . The authors demonstrated that this cross-linking increased the efficacy of CD4-mediated viral entry inhibition.…”
Section: Discussionmentioning
confidence: 99%